Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian Micellar Water Garnier pada Marketplace Shopee : Survei pada Konsumen Micellar Water Garnier di Kota Tasikmalaya - Alda Meila Tarisha; Kusuma Agdhi Rahwana; Ai Kusmiati Asyiah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The aim of this research is to determine and analyze the influence of online customer reviews, online customer ratings and purchasing decisions for micellar water garnier products on the Shopee marketplace in Tasikmalaya City. The research method used is quantitative with a causality method and a survey approach, data obtained through distributing questionnaires to 100 respondents. Sampling used non-probability, precisely using purposive sampling and the analysis method used was multiple linear regression. The test results show that simultaneously online customer reviews and online customer ratings have a significant effect on purchasing decisions. Online customer reviews partially have a significant effect on purchasing decisions and online customer ratings have a significant effect on purchasing decisions.